The Effect of Financial Performance and Sales Growth on Financial Distress - Nur aisyah, Siti; Hotang, Keri Boru (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2026)
Purpose – This study aims to obtain empirical evidence regarding the effect of profitability, leverage, firm size, and sales growth on financial distress. Design/methodology/approach – This research employs a quantitative approach. The sample consists of 13 property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2014–2024. The analytical technique used to test the hypotheses is multiple regression analysis with the assistance of Eviews 9 software. Findings – The results show that profitability has a significant effect on financial distress, meaning that the higher the profit earned, the lower the likelihood of the company experiencing financial difficulties. Leverage has a significant effect on financial distress, indicating that the higher the proportion of debt, the greater the risk of financial distress borne by the company. Firm size also has a significant effect on financial distress, suggesting that larger companies tend to have greater capacity to withstand financial pressure. Conversely, sales growth does not have a significant effect on financial distress. This can be explained by agency theory, in which managers often focus on increasing sales to demonstrate good performance to investors, but such an increase does not necessarily improve profit or cash flow. Thus, even when sales increase, the company’s financial condition does not automatically improve, and the risk of financial distress may still remain. Research limitations/implications – This study discusses financial distress and other factors such as profitability, leverage, firm size, and sales growth with a focus on the property and real estate sector. It applies the Altman Z-Score (1968) as a measure of financial distress.